Prevalence and detection of Vibrio spp. and Vibrio cholerae in fruit juices and flavored drinks - Anyi, Ubong; Robin, Tunung; Ahmad, Noorlis; Nillian, Elexson; Tuan Chilek, Tuan Zainazor; Mohamad Ghazali, Farinazleen; Nakaguchi, Yoshitsugu; Nishibuchi, Mitsuaki; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
In this study, the prevalence of Vibrio spp. and V. cholerae in flavored drinks and fruit juices sold at hawker stalls and in restaurants were determined using the most probable number (MPN) method and polymerase chain reaction (PCR) assay. One hundred and twenty drinks samples of four types of drinks (Iced Milk Rose Syrup, n=25; Iced Milk Corn Syrup, n=20; Apple Juice, n=37 and Iced Carrot Milk, n=28) were collected at two different settings; mainly hawker stalls and restaurants. Upon analysis, the prevalence of Vibrio spp. and V. cholerae in fruit juices and flavored drinks for hawker stalls were 93.3% and 36.7%, respectively whereas for the restaurants, were 93.3% and 20% respectively. Overall, the prevalence of Vibrio spp. and V. cholerae in all the drink samples were 93.3% and 28.3% respectively, highlighting the needs for the improvement of the hygiene and sanitation practice in the settings being studied.